2015
DOI: 10.1002/oby.21172
|View full text |Cite
|
Sign up to set email alerts
|

Improving diabetes outcomes through lifestyle change – A randomized controlled trial

Abstract: Objective: To compare a diabetes group lifestyle intervention (GLI) with dietitian referral for medical nutrition therapy (RD) for weight loss in the usual care setting. Methods: Randomized clinical trial was conducted with 57 primary care patients with type 2 diabetes and body mass index (BMI) >25 kg/m 2 who received either a dietitian-led 19-week GLI adapted from the Look AHEAD study or RD. Outcome measures include 6-month and 1-year weight loss, changes in medications, glycemic control, cardiac risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 18 publications
0
72
0
Order By: Relevance
“…Five trials [31,32,36,39,S18] selected participants after a run-in phase lasting between 3 days [36] and 6 months [S18] during which time participants confirmed their commitment by activities such as completing food and exercise diaries, or attending regular diabetes education sessions.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five trials [31,32,36,39,S18] selected participants after a run-in phase lasting between 3 days [36] and 6 months [S18] during which time participants confirmed their commitment by activities such as completing food and exercise diaries, or attending regular diabetes education sessions.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All five trials providing extra contacts with intervention staff, if required, saw significant effects on weight [38,40,45,S14,S19]. Eight of the nine trials providing personalized feedback showed significant effects on weight/BMI [28,32,39,42,45,S4,S15, S19].…”
Section: Weight and Bmimentioning
confidence: 99%
See 1 more Smart Citation
“…Greater success with maintaining a lower weight after significant weight loss (“secondary weight maintenance”) is possible via intensive and costly interventions including long‐term behavioural support . There is a need to research programmes that maintain success with lower financial expense . Importantly, research must also focus on “primary weight maintenance, ” that is, strategies to avoid weight gain and remain a healthy weight throughout life.…”
Section: Introductionmentioning
confidence: 99%
“…It is against this backdrop that we view the impressive work of Delahanty and colleagues to adapt the Look AHEAD intensive lifestyle intervention (ILI) for the primary care setting. The ILI demonstrated significant weight loss of 8.6% and cardiovascular risk factor improvement at 1 year among individuals with obesity and type 2 diabetes (T2D) .…”
mentioning
confidence: 99%